Implementation of POJK 51 and CSR Disclosure in the Sustainability Reports of Agricultural and Aquaculture Sector Companies in 2022 - Sitandung Kombong, Christine Bawaeda; Kurniawati, Kurniawati (Publikasi Indonesia, 2025)
This study examines the implementation of POJK 51 and SDGs disclosure in the 2022 sustainability reports of companies in the agriculture and aquaculture industries' D sector. Using data from the Indonesia Stock Exchange's official website, 48 companies were sampled and analyzed using content analysis. Results show that most companies have achieved a high category in POJK 51 implementation, indicating strong awareness of SDGs practices. However, about 40% are in the medium category. Distribution of POJK 51 implementation percentages varies significantly among companies. While the majority disclose SDGs at a medium level, some exhibit low levels. Variations in SDGs disclosure percentages highlight differing levels of engagement, suggesting areas for sustainability reporting improvement. Overall, the research provides valuable insights for stakeholders and the industry to enhance commitments to sustainability practices and SDGs attainment.